Safety and impact on training of the influenza vaccines in elite athletes participating in the Rio 2016 Olympics - Krzywanski, J.; Kuchar, E.; Pokrywka, A.; Mikulski, T.; Pilchowska, I.; Mlynczak, M.; Krysztofiak, H.; Jurczyk, J.; Ziemba, A.; Nitsch-Osuch, A. (Clinical Journal of Sport Medicine, 2021)
OBJECTIVE:The aim of the study was to evaluate the safety and tolerance of influenza vaccines for the northern and southern hemispheres in Polish elite athletes participating in the Rio 2016 Olympics. DESIGN:Prospective, observational, cohort study. SETTING:Institutional level. PARTICIPANTS:Ninety-seven athletes vaccinated only with the northern hemisphere vaccine; 98 athletes received the southern hemisphere vaccine alone, whereas 39 athletes were vaccinated with both vaccines. INTERVENTIONS:The athletes were vaccinated with a trivalent, inactivated influenza vaccine recommended for the northern hemisphere 2015/2016 and then with the vaccine recommended for the southern hemisphere 2016. Athletes kept a diary of adverse events and effects (if any) on training for 6 days after vaccination. MAIN OUTCOME MEASURES:The percentage of general and local adverse events, number of lost or modified training sessions. RESULTS:Significantly more local adverse events (pain and redness) were found in the group immunized with the vaccine for the northern hemisphere. There were no differences in the frequency of general adverse events and influence on training between groups. Of total 273 athletes who had 1911 training days during 6 days after vaccination, 6 athletes (2.2%) lost 13 training days (0.7%) and 16 athletes (5.9%) had to modify 34 (1.7%) training days within first 2 days after vaccination. CONCLUSIONS:Athletes tolerated influenza immunization well. If they are going to travel to the other hemisphere during the influenza season, the use of the second influenza vaccine should be advised. Athletes should anticipate modification of trainings for 2 days after vaccination.